Evaluation of Infection In First Three Months of Renal Transplant A Hospital Based Study - Islam, Md Nazrul; Akter, Mursheda; Bhuiyan, Ferdous Kamal; Ahmed, Parvez Iftekhar; Rahman, Md Mostafizur; Arefin, Md Shakib uz Zaman; Rashid, Harun Ur (Journal of Dhaka Medical College, 2015)
Background:The success of renal transplantation depends on a compromise between achieving sufficient immunosuppression to avoid rejection of the graft and maintaining a sufficient level of immuno competence to protect the recipient from infection. This study was undertaken to findout the prevalence of infection of renal allograft, to determine cause of infection, isolation of organism, antibiotic sensitivity and to evaluation of fate of infection within first three months of post transplant period. Methods: All the subjects of this study had received live related renal transplantation. Triple immunosuppressive therapy was started day before transplantation. Before enrollment in this study, all base line investigations of recipient and donor were done. All the patients were investigated at 3rd, 7th, 14th, 21st, 28th day, end of 2nd and 3rd month and whenever infection was suspected any time within first 3 months of transplantation. Patients of primary graft failure were excluded from this study. Results were expressed as mean ± standard deviation (mean ± SD).Fisher exact test or chi-square tests were performed for data analysis. All analysis were done using SPSS windows package and p value <0.05 were considered significant. Results:In the present study, 71% patients had suffered from infection within first 3 months of post transplant period. Among them 71% occurred during hospital stay. Infection rate was 62% at the first month followed by 25% in 2nd month and 13% at 3rd month. Ninty six percent causes were bacterial infection and 4% were viral infection. Bacterial infection included urinary tract infection (79%), respiratory tract infection (6%), septicaemia (7%) and wound infection (4%). During follow up, most of the UTI were of bacterial origin, male and female had suffered from similar incidence of UTI (72% vs 69%), that was statistically insignificant (p=NS). Most of the episodes of UTI (90%) were associated with bacteriuria caused by E.coli. Conclusion: In the present study showed that, infection was the most common complication within first 3 months of transplant patient. UTI was the most common and remains major cause of morbidity of renal transplant recipients. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 153-156